Food ordering system using QR code - Nor Syamira Akilah, Mohamad Jaafar (2018)
Food ordering are very important service for a restaurant. This is a service that offered by a waiter to a customer who came to the restaurant. There are some problems that maybe to face by using the traditional food ordering. Problems that occur are misunderstanding between the waiter and the customer when taking the order. Besides, the customer need to wait for a moment for a waiter to come to take the order. The current system are using the traditional way which using a piece of paper and menu paper to take an order from the customers. Therefore, Food Ordering System using QR Code technology is a real time ordering system to manage the order process for the restaurant. Therefore, the food ordering system using QR Code technology is an alternative to solve that problem. The system use smartphone as a platform because nowadays smartphone is a necessary for everyone. The customers need to scan the QR Code on the menu paper that provided by the restaurant. By using this system also, the customer can confirm the ordered item. Besides, the staff of the restaurant also can manage the menu and view order list.